Evaluation of the Use of Prophylactic Antibiotics in Sectio Caesarea Patients at Scholoo Keyen Hospital, South Sorong Regency in 2022 - Nurwahyuni; Lukman Hardia; Angga Bayu Budiyanto (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
A caesarean section is an attempt to remove the fetus through surgery on the uterine wall. Problems during surgery are infection, bleeding, surgical complications, and morbidly adherent placenta. Approximately 90% of postoperative morbidity is caused by ILO. Treatment for ILO is by administering antibiotics. Prophylactic are antibiotics given 30-60 minutes before a caesarean section. The aim of this research is to find out what antibiotics are given and how to evaluate the use of prophylactic in cesarean patients based on medical record data at Scholoo Keyen Hospital in 2022. This research is a descriptive evaluative method to get an idea of the presentation rate of rofile and characteristics of medical data records at Scholoo Keyen Hospital in 2022. Data analyzed using descriptive data. The results show that from 152 samples, the most widely used prophylactic was ceftriaxone (69.7%). Evaluation of the appropriateness the use of prophylactic in cesarean patients with the hospital formulary being appropriate and compared with Gudline POGI, and ASHP therapeutic. The results were obtained according to the right indication, the right patient, the right route of administration, and the right time of administration was appropriate. While the right medicine and the right dose is not appropriate.